Les « TIC vertes » : effet de mode ou tendance lourde, oxymore ou solution durable ? - Fabrice Flipo (Netcom)
ICT are not synonymic any more of weightlessness, hence the current fashion for "green IT". We demonstrate some of the stakes involved in green consumption practices.